2022
DOI: 10.1155/2022/1132452
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic Value of Creatine Phosphate and Inflammatory Markers for Mitral Valve Replacement: A Systematic Review and Meta-Analysis

Abstract: Purpose. The prognosis of mitral valve replacement is an important clinical issue and may produce unexpected mortality rates if not properly addressed. The postoperative examination results have important prognostic implications. This study was designed to determine the prognostic value of phosphocreatine and inflammatory markers after mitral valve replacement. Method. Comparison and analysis of the data obtained using SPSS software. The computer retrieved PubMed, Science Citation Index (SCI), Embase, VIP, CNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%